PERAN PEMERINTAH DALAM MENJAMIN KEAMANAN MANUSIA DALAM UPAYA REVITALISASI KAWASAN HULU DAS CITARUM DI DESA TARUMAJAYA KECAMATAN KERTASARI MELALUI PERATURAN PRESIDEN NOMOR 15 TAHUN 2018 - Neneng Widya Amellia; Wawan Budi Darmawan (Jurnal Academia Praja, 2025)
Environmental issues related to the exploitation of an area in the upstream part of the Citarum River Basin by a group of encroachers have resulted in massive environmental damage and impacted the safety of other people living and occupying areas near the Citarum River Basin. This has drawn serious attention from the government, prompting it to take steps to revitalize areas along the Citarum River Basin, from upstream to downstream. This action was taken through Presidential Regulation No. 15 of 2018, as an effort to ensure environmental security and human safety. However, in some areas, this government revitalization policy has drawn cynical responses from some, as it is perceived to only benefit certain parties. This research aims to identify the role of the central and regional governments in guaranteeing the rights of individuals affected by Presidential Regulation No. 15 of 2018. This research utilizes several theories and concepts, including the UNDP's concept of human security, as well as supporting theories such as the securitization theory of Buzan, Waever, and Wilde, and the environmental security theory of Bryant and Bailey, as well as Peterson and Lay. The research method used in this study is descriptive with a qualitative approach. Data collection techniques used were observation, in-depth interviews, and documentation studies. The results of the study indicate the involvement of several actors, including government officials, namely sub-district heads and village heads, who have granted permits to investors for land use and management in the upstream Citarum Watershed area of ​​Tarumajaya Village. This is intended to improve the economic well-being of Tarumajaya Village residents, Kertasari District. This also includes government-planned efforts to relocate residents to more suitable locations.